2004
DOI: 10.1038/sj.gt.3302362
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Progress and Prospects: Episomally maintained self-replicating systems

Abstract: The use of nonviral gene therapy vectors has been hampered by low level of transfection efficiency and lack of sustained gene expression. Episomal self-replicating systems may overcome these hurdles through their large packaging capacity, stability and reduced toxicity. This article reviews three classes of episomal molecules that have been tested with possible therapeutic genes: (1) self-replicating circular vectors, containing the Epstein-Barr virus (EBV) elements oriP and EBNA1; (2) small circular vectors c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 36 publications
(45 reference statements)
1
49
0
1
Order By: Relevance
“…40,41 Additionally, no prolonged luciferase expression or DNA persistence was observed after intravenous lung administration of an S/MAR-containing pEPI-1 vector with a CMV-driven expression cassette. 42 Together with our data, these results suggest that S/MAR-containing vectors are prone to promoter attenuation in vivo if not combined with constitutive or tissue-specific promoters. The exact mechanism of how an S/MAR element may protect a particular promoter in vivo from methylation now requires further characterization but it can be assumed that cell-or tissue-specific factors play a decisive role in this process.…”
Section: Persistent Expression In Vivo From S/mar Plasmidsupporting
confidence: 84%
“…40,41 Additionally, no prolonged luciferase expression or DNA persistence was observed after intravenous lung administration of an S/MAR-containing pEPI-1 vector with a CMV-driven expression cassette. 42 Together with our data, these results suggest that S/MAR-containing vectors are prone to promoter attenuation in vivo if not combined with constitutive or tissue-specific promoters. The exact mechanism of how an S/MAR element may protect a particular promoter in vivo from methylation now requires further characterization but it can be assumed that cell-or tissue-specific factors play a decisive role in this process.…”
Section: Persistent Expression In Vivo From S/mar Plasmidsupporting
confidence: 84%
“…Alternatively or in addition to, silencing of the CMV promoter could also account for this, especially since pCMV has been reported to be prone to silencing in primary human cells. 43,44 Given that the presence of an active transcription unit upstream of the S/MAR is believed to play a very important role in vector's maintenance, 20,27 the expression cassette of this plasmid is likely to have an impact on properties of the vector other than transgene expression rate and it is possible that the use of alternative constitutive viral promoters or tissue-specific promoters might also enhance vector stability. We are currently examining this hypothesis by testing the effect that different transcriptional cisregulatory elements have on overall vector performance in CD34 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tessadori et al [178] concluded that the regulatory mechanisms that act on episomal genes seem to be similar to those that control host genes. The episomal chromatin undergoes the same modifications as the host chromatin e.g.…”
Section: Nonviral Chromatin Tethering Factorsmentioning
confidence: 99%